High-performance four-element self-decoupled MIMO antenna system for N260 band applications - Kiani, Saad Hassan; Mohd Ibrahim, Imran; Bhadravathi Ghouse, Parveez Shariff; Sehrai, Daniyal Ali; Abdullah, Mujeeb; Ali, Tanweer; Algarni, Abeer Dhafer; Elmannai, Hela (Springer, 2025)
This paper introduces a wideband multiple-input multiple-output (MIMO) antenna designed for 5G applications. The antenna achieves a wideband response by incorporating multiple slots into the radiating element, providing an operating bandwidth of approximately 4.5 GHz centered around 37 GHz, which covers the widely recognized 5G N260 band. Notably, the design features a full ground plane. To address the high throughput requirements of modern wireless communication, the antenna is expanded into a four-port MIMO configuration, with an edge-to-edge gap of just 0.026 wavelengths (λo) between the elements. Despite this small separation, a remarkable isolation exceeding 25 dB is achieved. With its adequate bandwidth, peak gain of nearly 13.4 dB, and satisfactory MIMO performance metrics, the proposed MIMO antenna is a promising candidate for 5G applications.